GSK 650394 Inhibits Osteoclasts Differentiation and Prevents Bone Loss via Promoting the Activities of Antioxidant Enzymes In Vitro and In Vivo. (17th September 2022) - Jin, Lin-Yu; Huo, Shi-Cheng; Guo, Chen; Liu, Hai-Ying; Xu, Shuai; Li, Xin-Feng
Abstract : Osteoporosis (OP) is one of the most common bone disorders among the elderly, characterized by abnormally elevated bone resorption caused by formation and activation of osteoblast (OC). Excessive reactive oxygen species (ROS) accumulation might contribute to the formation process of OC as an essential role. Although accumulated advanced treatment target on OP have been proposed in recent years, clinical outcomes remain unexcellence attributed to severe side effects. The purpose of present study was to explore the underlying mechanisms of GSK 650394 (GSK) on inhibiting formation and activation of OC and bone resorption in vitro and in vivo. GSK could inhibit receptor activator of nuclear- κ B ligand (RANKL-)-mediated Oc formation via suppressing the activation of NF- κ B and MAPK signaling pathways, regulating intracellular redox status, and downregulate the expression of nuclear factor of activated T cells c1 (NFATc1). In addition, quantitative RT-PCR results show that GSK could suppress the expression of OC marker gene and antioxidant enzyme genes. Consistent with in vitro cellular results, GSK treatment improved bone density in the mouse with ovariectomized-induced bone loss according to the results of CT parameters, HE staining, and Trap staining. Furthermore, GSK treatment could enhance the capacity of antioxidant enzymes in vivo. In conclusion, this study suggested that GSK could suppress the activation of osteoclasts and therefore maybe a potential therapeutic reagent for osteoclast activation-related osteoporosis.